Pengaruh Economic Value Added Terhadap Tingkat Pengembalian Saham pada Perusahaan yang Tergabung dalam LQ-45 - Harris Hansa Wijaya; Lauw Tjun Tjun (Universitas Kristen Maranatha, 2009)
Economic Value Added (EVA) is a financial performance measurement that is assumed deal with investors’ expectation. It is because EVA not only observes from rate of return but also from company’s risk level. The purpose of this research is to know the influence of EVA to stock’s rate of return. The sample of this research is 35 companies that listed in LQ45. Data are analyzed used regression analysis. The result indicates that EVA have influence to stock’s rate of return. Keywords: Financial performance, Economic Value Added, stock’s rate of return.